Is God a moral monster? : making sense of the Old Testament God - Copan, Paul (Grand Rapids, Mich. : Baker Books, 2011)
Apologist Paul Copan takes on some of the most vexing accusations of our time, including that God is arrogant and jealous, punishes people too harshly, is guilty of ethnic cleansing, oppresses women, and endorses slavery. He also challenges the accusation that Christianity causes violence. Copan not only answers God's critics, he also shows how to read both the Old and New Testaments faithfully, seeing an unchanging, righteous, and loving God in both. --from publisher description
Who are the new atheists? -- The new atheists and the Old Testament God -- Great appetite for praise and sacrifices? Divine arrogance or humility? -- Monumental rage and kinglike jealousy? Understanding the covenant-making God -- Child abuse and bullying? God's ways and the binding of Isaac -- God's timeless wisdom? incremental steps for hardened hearts -- The Bible's ubiquitous weirdness? Kosher foods, kooky laws? (I) -- The Bible's ubiquitous weirdness? Kosher foods, kooky laws? (II) -- Barbarisms, crude laws, and other imaginary crimes? Punishments and other harsh realities in perspective -- Misogynistic? Women in Israel -- Bride-price? Polygamy, concubinage, and other such questions -- Warrant for trafficking in humans as farm equipment? (I) : slavery in Israel -- Warrant for trafficking in humans as farm equipment? (II) : challenging texts on slavery -- Warrant for trafficking in humans as farm equipment? (III) : slavery in the New Testament -- Indiscriminate massacre and ethnic cleansing? The killing of the Canaanites (I) -- Indiscriminate massacre and ethnic cleansing? The killing of the Canaanites (II) -- Indiscriminate massacre and ethnic cleansing? The killing of the Canaanites (III) -- The root of all evil? Does religion cause violence? -- Morality without a lawgiving God? The divine foundation of goodness -- We have moved beyond this God (haven't we?) : Jesus as the fulfiller of the Old Testament
Includes bibliographical references (pages 235-252)
Keywords: Bible. -- Theology; Ethics in the Bible; Apologetics